Generating mathematical strategies shows evidence of a serial order effect - Shaw, Stacy T.; Yeghyayan, Anahit A.; Ballenger, Eric; Ramirez, Gerardo (Frontiers in Education, 2024)
This study investigated whether performance on a mathematical strategy-generating task showed evidence for a serial order effect (decreasing fluency but increasing originality and creativity of strategies over time). One-hundred and fifty-five undergraduate students generated as many strategies as they could to solve a three-digit subtraction problem for 8 min, and the resulting strategies were evaluated using fluency and originality indexes that were heavily informed by research on creativity. Results showed evidence for a serial order effect, such that strategy fluency decreased across the working period, but later strategies were rated as more original/creative. These results demonstrates that classroom practices that encourage strategy generation can be a useful tool to help students think more creatively in mathematics.